2015
DOI: 10.3390/ijerph120302941
|View full text |Cite
|
Sign up to set email alerts
|

Association of Light Exposure on Physical Activity and Sedentary Time in Young People

Abstract: Background: To investigate whether light exposure was associated with objectively measured physical activity (PA) and sedentary behaviour in young people. Methods: Participants (n = 229, 46.7% female) were young people (mean 8.8 years [SD ± 2.2]) from the borough of Camden, UK. Daily sedentary time, moderate and vigorous PA (MVPA) and light exposure were measured using a tri-axial accelerometer with an ambient light sensor during the summer. Multiple linear regression models examined associations between avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(42 reference statements)
1
12
1
2
Order By: Relevance
“…3, indicating that some participants may have spent more time inside, away from the increased sunlight. Wide variations in individual light exposure have also been documented in previous studies (Aggio et al, 2015; Schmalwieser et al, 2010; Thieden, 2008). Future studies in larger and more generalizable samples in conjunction with light exposure measurements would strengthen the external validity of our findings.…”
Section: Discussionsupporting
confidence: 71%
“…3, indicating that some participants may have spent more time inside, away from the increased sunlight. Wide variations in individual light exposure have also been documented in previous studies (Aggio et al, 2015; Schmalwieser et al, 2010; Thieden, 2008). Future studies in larger and more generalizable samples in conjunction with light exposure measurements would strengthen the external validity of our findings.…”
Section: Discussionsupporting
confidence: 71%
“…Al comparar los METs entre género los datos fueron similares entre los grupos, no obstante al momento de analizar el tiempo dedicado a las diferentes intensidades de la AF, los niños le brindaron 13.46% más tiempo de actividad moderada que las niñas; en cambio, ellas le dedicaron 13.79% más del tiempo en actividades ligeras. Las diferencias de género e intensidad han sido reportados también por otros estudios previos (Ridgers et al, 2010;Dyment, Bell, y Lucas, 2009;Patnode et al, 2010;Dessing et al, 2013;Baquet et al, 2014;Aggio, Smith, Fisher, y Hamer, 2015), donde se concuerda que los niños realizan AF diferente que las niñas. Tal vez los niños sean más afines a realizar AF en deportes muy populares y competitivos como el fútbol; y es posible que las niñas se involucren en otras actividades que requieren menos intensidad, como lo puede ser actividades de tipo social.…”
Section: Discussionunclassified
“…Con relación a las conductas sedentarias el porcentaje de tiempo dedicado para este fin fue por debajo del 3%, mucho menor a los resultados reportados por Dessing et al (2013), que encontraron valores por encima del 70% en niños de primaria. Además, los resultados del presente estudio no mostraron diferencias entre género con respecto a esta variable, aunque en la literatura las mujeres poseen conductas más sedentarias que los niños durante el recreo (e.g., Baquet et al, 2014;Aggio et al, 2015). El recreo ofrece una serie de alternativas que contribuyen a que los alumnos se involucren en AF.…”
Section: Discussionunclassified
“…Researchers concluded that average light exposure is positively associated with time in MVPA and negatively associated with sedentary time. Therefore, one may conclude that increasing daylight exposure might be a useful intervention strategy for promoting physical activity and consequently vitality and performance among young Students [35].…”
Section: Natural Light and Students' Academic Performancementioning
confidence: 99%
“…Aggio et al [35] evaluated the impact of light exposure on the productivity of 229 students from the perspective of physical activity and sedentary time (age mean = 8.8 years) in Camden, UK. To investigate it, daily sedentary time, Moderate and Vigorous Physical Activity (MVPA) and light exposure were measured daily by using a tri-axial accelerometer with an ambient light sensor during the summer.…”
Section: Natural Light and Students' Academic Performancementioning
confidence: 99%